Factors Influencing the Lending Behavior of Commercial Banks in Nepal - Kharel , Tika Ram; Poudel, Shiva Raj; kharel , Pratik (Journal of Research in Education, 2025)
This study examines the major factors affecting the lending behavior of commercial banks in Nepal. It is based on analysis of the data from five investing banks encompassing the ten-year period from 2014/15 to 2023/24. The research employed both descriptive and causal-comparative research designs. The study is based on the secondary data extracted from annual reports and financial statements. Statistical analysis was carried out using SPSS version 27. The sampled banks are Prabhu Bank, Nepal Investment Mega Bank, NMB Bank, NIC Asia Bank, and Kumari Bank Limited. The analysis is concerned with how several independent variables Cash Reserve Ratio (CRR), Capital Adequacy Ratio (CAR), Interest Rate Spread (IRS), Total Deposits (TD), and Inflation Rate (INF) are related to the dependent variable, Loans and Advances (LA). The results disclose a moderate negative association between CRR and LA, implythat higher reserves reduce investing activity. In counterpoint, CAR shows a strong positive connection with investing, involving that well-capitalized banks are more capable of amplifying credit. IRS displays only a poor relationship, while TD has a strong positive influence, meaning banks with larger deposit bases attend to issue more loans. Similarly, inflation (INF) is moderately negatively related to investing, indicating that higher inflation can diminish credit growth. Overall, the findings show that CAR significantly enhances investing, whereas IRS has a negative effect. Total deposits have a strong positive impact, while CRR and inflation are not statistically significant predictors. The study concludes that CRR, IRS, TD, and INF play major roles in creating the investment behavior of Nepalese commercial banks.